I actually think its b cause it can't be d (thats obvious) yh........but i might be wrong
Answer:
x(3y - 1) and (2a - 3)(2a + 3)
Step-by-step explanation:
(1)
3xy - x ← factor out x from each term
= x(3y - 1)
(2)
4a² - 9 ← is a difference of squares and factors in general as
a² - b² = (a - b)(a + b) , then
4a² - 9
= (2a)² - 3²
= (2a - 3)(2a + 3)
Answer:
Step-by-step explanation:
Just use the distributive property.
(4y^2-3)(4y+3)
= 4y^2(4y+3) - 3(4y+3)
= 16y^3 + 12y^2 - 12y - 9
Answer:
ok ill try
Step-by-step explanation:
Think first is Distributive Property
Combine any LIKE TERMS
Isolate the VARIABLE
By using INVERSE
Check your ANSWER
I think these are the answers hope it helps!